2022
DOI: 10.1093/jpids/piac072
|View full text |Cite
|
Sign up to set email alerts
|

Use of Host Response to Refine the Diagnosis of Group A Streptococcal Pharyngitis

Abstract: Background Current diagnostic tests for pharyngitis do not distinguish between symptomatic group A Streptococcus (GAS) infection and asymptomatic colonization, resulting in over-diagnosis and unnecessary use of antibiotics. We assessed whether measures of host response could make this distinction. Methods We enrolled 18 children with pharyngitis having Centor scores of 4 or 5 and 21 controls without pharyngitis or other acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Acinetobacter baumannii is a common clinical pathogen, which accounted for the top three respiratory tract isolates in 2016–2019, according to the China Antimicrobial Surveillance Network. Multidrug-resistant strains of HAP have become more frequent in clinical settings ( 14 , 19 ), contributing to a 52% Ab mortality rate ( 4 ). Hence, early identification of Ab colonization and infection is vital to prevent disease progression, reduce antibiotic abuse, and halt bacterial drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acinetobacter baumannii is a common clinical pathogen, which accounted for the top three respiratory tract isolates in 2016–2019, according to the China Antimicrobial Surveillance Network. Multidrug-resistant strains of HAP have become more frequent in clinical settings ( 14 , 19 ), contributing to a 52% Ab mortality rate ( 4 ). Hence, early identification of Ab colonization and infection is vital to prevent disease progression, reduce antibiotic abuse, and halt bacterial drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical experimental data and diagnosis and treatment guidelines for distinction of bacterial infection and colonization are lacking. Clinicians identify pulmonary Ab infection or colonization based on the results of bacterial culture, white blood cell count (WBC) and neutrophil classification (N%), C-reactive protein (CRP), procalcitonin (PCT), and other plasma biomarker detection results combined with time consuming and subjective imaging and symptoms analysis ( 4 ). This method not only wastes time but also depends on the subjective judgment of doctors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This experimental method had a specificity and sensitivity of 88% and 87.5%, respectively, for detecting GAS pharyngitis 37. Host transcriptome profiles have recently been explored to distinguish symptomatic GAS pharyngitis from colonisation 38. Using peripheral blood RNA sequencing, one study demonstrated that host gene expression in symptomatic GAS pharyngitis was significantly different from asymptomatic colonisation 38…”
Section: Future Directions In Gas Pharyngitismentioning
confidence: 99%
“…Two of those datasets were related to the acute phase of infection, including both viral and bacterial infection in each dataset (GSE161731 and GSE176262) [12,13]. One dataset was related to the comparison of active infection and inactive colonization of group A streptococcal (GSE158163) [14]. Another dataset was related to the comparison of the acute phase and convalescence phase of Leptospirosis (GSE72946) [15].…”
Section: Analysis Of Virsig and Bacsig In All Phases Of Acute Infectionmentioning
confidence: 99%